SIMULASI DAN PERANCANGAN BILAH TURBIN ANGIN SAVONIUS HELIKS DENGAN MEMANFAATKAN FENOMENA ANGIN PADA GEDUNG TINGGI - Irfan Muhammad (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
The shape of the earth's uneven topography causes many phenomena to occur that can deflect and change the character of wind speed. This phenomenon can occur due to natural factors and human intervention factors. The presence of a high-rise building complex is one of the causes of the downwash and venturi effect phenomena. Both phenomena are famous for producing wind gusts that are significant enough to disturb pedestrian comfort. Therefore, in this study the author will calculate the change in wind speed character with the influence of these two phenomena as the potential driving energy for three variants of helical type vertical axis wind turbines with Computational Fluid Dynamic (CFD) simulation media. The simulation process is divided into two stages, the first is the author runs a simulation of the effect of wind phenomena on the natural wind speed character, which shows an increase in wind speed of 40%. And the last is a simulation of the power output of each wind turbine variant using wind speed data in the previous stage. The results show that a helical type vertical axis wind turbine with a normal blade can produce an optimal power of 447,8 watt.